ANALYSIS OF STUDENTS’ READING INTEREST AND THE ROLE OF TEACHERS IN IMPROVING READING LITERACY AT SDN 10 RIO PAKAVA - Ingrid Humaira; Nashrullah; Eva Setya Rini; Zulnuraini (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to analyze the reading interest of fourth-grade students at SDN 10 Rio Pakava and to explain the role of teachers in improving students’ reading literacy. The approach used in this research is a qualitative approach. The subjects of this study were 10 fourth-grade students of SDN 10 Rio Pakava. The research design refers to the theory developed by Creswell (2008), which includes the stages of describing, analyzing, and interpreting students’ reading interest and the role of teachers in improving reading literacy at SDN 10 Rio Pakava. Data were collected through observation, interviews, questionnaires, and documentation, and then analyzed qualitatively. The results of the study indicate that the reading interest of fourth-grade students at SDN 10 Rio Pakava is generally in the high category, with an average percentage of 63%. This is based on the indicators of enjoyment (66.67%), concentration of attention (73.33%), time allocation for reading (56.67%), and reading motivation (26.67%). Teachers have a very important and strategic role in improving the reading literacy of fourth-grade students at SDN 10 Rio Pakava through reading habituation, the provision of reading corners, guidance during reading activities, motivation, and the creation of a conducive classroom atmosphere.